Clarithromycin and Amoxicillin Effect on Helicobacter Pylori-Infected Oxidative DNA Damage - Zinah Shakir Shallal (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Epidemiological studies reveal that the risk of developing stomach cancer increase by Helicobacter pylori infection, and scientists assume that oxidative DNA damage caused by the bacteria is to blame. Oxidative DNA damage in Helicobacter pylori-infected cases was measured before and after two weeks of clarithromycin and amoxicillin (1 g/day) +amoxicillin (1 g/day) treatment using DNA chain fractures and form amidoprimidine DNA glycosylase (fpg)-sensitive regions. After treatment, it was found that the Comet method's measurement of the frequency of fpg-sensitive regions decreased (P0.001), while the frequency of DNA chain breaks remained unchanged. A favorable connection between age and prevalence off fpg-sensitive areas was found (r = 0.59, P 0.05). The results suggest that lowering oxidative DNA damage through treatment with clarithromycin + amoxicillin in helicobacter pylori-infected individuals may lessen the risk of helicobacter pylori-mediated stomach cancer formation.